Here's the question you clicked on:
vetdoc
If f(x) = x − 4 and g(x) = 1/2x − 2, find f[g(−6)].
When you see f[g(x)], you're basically taking the result of g(x) and using that as the value of X in f(x). g(-6) = (1/2)(-6)-2 = ?
So, this is what you do. First you substitute -6 for the x 's in the second equation then you substitute what you get there for the x 's in the first equation.
g(-6) = (1/2)(-6)-2 = -5 f(g(-6)) = -5 - 4 = -9
so the answer is -9
I got -5 for the second equation. Then entered that in the first and got -9 for the first equation.